Synthesis and characterization of ( L- proline ) amino acid with (Mn+2 , Fe+2 , Co+2 , Zn+2 and Cd+2 ) (مجلة ديالى للبحوث الانسانية, 2022)
Thise paper includes the synthesis and characterization of the complexes of the amino acid (L-proline) = C5H9NO2) symbolized (proH)-with some metal . The ligand and metal ions were brought into reaction in ethanolic medium using (1:2) metal : ligand molar ratios as required.Products were found to be solid crystalline complexes, which have been Characterized through the following techniques : Melting points, Solubility, Molar conductivity